A Narrative Review of Stigma Related to Infectious Disease Outbreaks: What Can Be Learned in the Face of the Covid-19 Pandemic? - Saeed, Fahimeh; Mihan, Ronak; Mousavi, S. Zeinab; Reniers, Renate LEP; Bateni, Fatemeh Sadat; Alikhani, Rosa; Mousavi, S. Bentolhoda (Frontiers in Psychiatry, 2020)
Infectious disease pandemics are associated with social consequences and stigma that are noticeably similar in various health conditions, health systems, and cultures. Stigma impacts health-related outcomes, not only as a barrier to receiving the timely diagnosis and appropriate treatment but also as an important variable that increases mental health issues such as anxiety and depression. The COVID-19 outbreak has been associated with stigma too. Studying similarities as well as differences in the features of stigma observed in each outbreak can provide us with the knowledge and deeper understanding of the situation, which is necessary for approaching the issue comprehensively. The stigma needs to be addressed rigorously by professionals and health care providers as well as authorities. Here, we narratively review stigma due to some well-known infectious diseases and how it parallels to the current COVID-19 situation. After discussing its effects on both individuals and societies, we provide solutions to manage this important issue.